Absensi Qr Code Dosen Berbasis Mobile Di Pascasarjana Institut Kh.Abdul Chalim Mojokerto - Ida Oktavia Salsavana; Budiman Budiman; Winarti Winarti (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Attendance is a form of attendance data collection or the presence of a person or employee who is part of the reporting of an institution that contains attendance status data that is neatly arranged and arranged and easy to find. This study aims to build an attendance system with a QR code, and integrate it with Smartphone The application can be made using Android-based QR Code technology. The application that was made was named Absensi e_presensipascaikhac. The process of making the Attendance e_presensipascaikhac application using the Waterfall method. Testing was carried out at the INSTITUT KH Institute. ABDUL CHALIM in the Postgraduate Department of Islamic Education Management and Islamic Religious Education with a total of 25 lecturers and testing by lecturers and software for testing.